Understanding Age-Related Interference in Cognitive-Motor Dual-Task Performance: A Novel Approach. - Béraud-Peigné, Néva; Perrot, Alexandra; Maquestiaux, François; Maillot, Pauline (Experimental Aging Research)
Objectives: Cognitive tasks in dual-task (DT) tests can be either driven mainly by the environmental demands (an" environment-driven" mode of control) or guided mainly by the individual (a "self-generated" mode of control). Two new DT tests were conducted to determine the effect of cognitive task types (self-generated vs. environment-driven) on cognitive and motor interference in DT. Methods: An exploratory study was conducted with 17 older adults (OLD) and 15 adults (YOUNG) who completed three single-task (ST) tests – motor, cognitive environment-driven, cognitive self-generated – and 2 DT tests. Cognitive and motor DT Effect (DTE) were calculated. Results: The self-generated DTE was greater in the motor task than in cognitive tasks, especially for the OLD group. There was no difference for the environment-driven DTE. In the motor task, the self-generated task created more interference than the environment-driven task for all groups, but this was not the case for the cognitive task. Conclusions: Some ideas were devised for creating interference-efficient tests, like using cognitive self-generated and motor complex tasks. The study confirmed previous results on gait tasks with new information on motor complex tasks.